Detection and Stimulation of Child Development Questionnaire for 2-4 Years - Nira Wulansari; Fitri Ariyanti Abidin; Lenny Kendhawati; Fitriani Yustikasari Lubis; Ajeng Indri Hastuti; Fatima Rahmah (SEAMEO CECCEP, 2023)
Child development involves expected abilities to evolve at various age stages, encompassing motor, cognitive, language, emotional, and social aspects. These fundamental abilities serve as the building blocks for more intricate development. Delays in achieving these milestones can potentially impede later-stage development. This study aims to develop a suitable developmental screening tool for Indonesian children aged 2-4 years, facilitating accurate early detection of developmental delays. The instrument's development involves five stages: (1) Test Conceptualization, (2) Test Construction, (3) Test Tryout, (4) Analysis, and (5) Revision. In the first stage, The Gesell's developmental concept was used. Four child psychologists reviewed the instrument's content during the test construction phase, followed by a feasibility test conducted on four mothers. From an initial formulation of 91 items for ages 2-3 years and 85 items for ages 3-4 years, expert judgment and cognitive interviews led to the elimination of certain items, resulting in 71 items for ages 2-3 years and 75 items for age 3-4 years in the tryout version.The tryouts were performed on mothers who met the following inclusive criteria: have children aged 2-4 years with no history of prenatal, post-natal, or developmental delays, not clinically diagnosed psychological problem, and familiar with the Google form. One hundred eighty-six mothers (age range = 23-48 years, mean = 31 years) participated in the study. The tryout demonstrated the initial validity of all aspects of children's development aged 2-4 years (content validity index range = 0.83–1.00) and good reliability (range of internal consistency coefficient = 0.562-0.768) for each developmental aspect. Item analysis indicated that only a small number of items need to be eliminated or revised in both age groups. The results suggest the instrument is a promising tool to measure children development aged 2-4.